2017
DOI: 10.1016/j.mssp.2016.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Progress in doping semiconductor nanowires during growth

Abstract: The anisotropic growth of one-dimensional or filamental crystals in the form of microwires and nanowires constitutes a rich domain of epitaxy and newly enabled applications at different length and size scales. Significant progress has been accomplished in controlling the growth, morphology, and properties of semiconductor nanowires and consequently their device level performance. The objective of this review is two-fold: to highlight progress up to date in nanowire doping and to discuss the remaining fundament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 182 publications
0
37
0
Order By: Relevance
“…Exploitation of NWs in LEDs [5,6], solar cells [7,8], photodetectors [9], and other optoelectronic devices requires a controllable methodology for doping. Consequently, significant efforts have been put into the investigation of the NW doping process [10]. A specific feature of the VLS process is that dopants can incorporate either through the catalyst droplet * Corresponding author: teemu.hakkarainen@tuni.fi or via the vapor-solid (VS) growth on the NW sidewalls.…”
Section: Introductionmentioning
confidence: 99%
“…Exploitation of NWs in LEDs [5,6], solar cells [7,8], photodetectors [9], and other optoelectronic devices requires a controllable methodology for doping. Consequently, significant efforts have been put into the investigation of the NW doping process [10]. A specific feature of the VLS process is that dopants can incorporate either through the catalyst droplet * Corresponding author: teemu.hakkarainen@tuni.fi or via the vapor-solid (VS) growth on the NW sidewalls.…”
Section: Introductionmentioning
confidence: 99%
“…We distinguish between conventionally doped NWs, which are doped by adding Si during growth, and unconventionally doped NWs, which are doped by FIB implantation prior to growth. Depending on the solubility of the dopant in the liquid phase of the droplet and in the solid phase of the NW, the dopant is incorporated into the NW during growth . This changes among other things the chemical potentials of the liquid and solid phase whereby the kinetic growth processes are influenced.…”
Section: Resultsmentioning
confidence: 99%
“…128,133 In other words, the dopants result more complexities in III-V nanowire growths and cause nanowires' growths less controllable. 194,195 In my PhD study, understanding the effect of dopant on nanowire growth is one major objective.…”
Section: Doping Of Iii-v Nanowiresmentioning
confidence: 99%
“…It has been reported that dopants have remarkable influence on semiconductor nanowires growth rate. In some cases, it is the dopant that changes the catalyst supersaturation, which is the driving force for axial growth; in some cases, it is the dopant or the precursor that act 195 Doping may also impact on the structural characteristics of nanowires. Furthermore, it was found that dopants could modify the interfacial energy between catalyst and nanowire.…”
Section: The Effect Of Doping On Nanowire Growthmentioning
confidence: 99%
See 1 more Smart Citation